Assessment of visceral pain with special reference to chronic pancreatitis - Kuhlmann, Louise; Olesen, Søren Schou; Drewes, Asbjørn Mohr (Frontiers in Pain Research, 2022)
A thorough pain assessment is of utmost importance when managing pain in clinical practice as it is the foundation for defining pain in need of treatment, either interventional or pharmacological. Pain characteristics can also guide interventional strategies and help evaluate the effect of treatment. In research settings, standardized pain assessment is crucial to improve comparability across studies and facilitate meta-analysis. Due to the importance of thorough visceral pain assessment, this manuscript describes the key elements of pain evaluation focusing on chronic pancreatitis. Most studies in pain assessment have focused on somatic pain, and although chronic pain often shares characteristics between etiologies, some differences must be addressed when assessing visceral pain. Especially differences between somatic and visceral pain are apparent, where visceral pain is diffuse and difficult to localize, with referred pain aspects and often autonomic symptoms dominating the clinical picture. These aspects need to be incorporated into the pain assessment instrument. The manuscript will discuss the different ways of assessing pain, including unidimensional measurement scales, multidimensional questionnaires, and quantitative sensory testing. The advantages and challenges linked to the different methods will be evaluated.